Análise estatística das características físico-químicas do óleo isolante mineral em transformadores de distribuição - Hukuchima, Thiago (2014)
This study was carried out in order to statistically analyze physico-chemical characteristics of mineral insulating oils used in distribution transformers. Such analysis is exclusively aimed at the dielectric insulating fluid, evaluating its chromatographic graduation according to the deterioration of its physical-chemical attributes. Statistical Inference is the tool used for drawing conclusions from the data obtained in the process, since its concepts and methodologies are compatible with the study in question.